2019
DOI: 10.3390/plants8090315
|View full text |Cite
|
Sign up to set email alerts
|

The Interplay among Polyamines and Nitrogen in Plant Stress Responses

Abstract: The interplay between polyamines (PAs) and nitrogen (N) is emerging as a key factor in plant response to abiotic and biotic stresses. The PA/N interplay in plants connects N metabolism, carbon (C) fixation, and secondary metabolism pathways. Glutamate, a pivotal N-containing molecule, is responsible for the biosynthesis of proline (Pro), arginine (Arg) and ornithine (Orn) and constitutes a main common pathway for PAs and C/N assimilation/incorporation implicated in various stresses. PAs and their derivatives a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 98 publications
1
21
0
Order By: Relevance
“…Exogenous application of polyamine and/or inhibitors of enzymes which are involved in polyamine biosynthesis also hints towards a possible role of such compounds in plant adaptation or defense process in response to environmental stresses [76]. Moreover, studies involving either transgenic overexpression or loss of function mutants support the protective, adaptive, or defensive role of polyamines in plant's response to various abiotic stresses [76,77].…”
Section: Intracellular Osmotic Adjustment and Osmoprotectantsmentioning
confidence: 99%
“…Exogenous application of polyamine and/or inhibitors of enzymes which are involved in polyamine biosynthesis also hints towards a possible role of such compounds in plant adaptation or defense process in response to environmental stresses [76]. Moreover, studies involving either transgenic overexpression or loss of function mutants support the protective, adaptive, or defensive role of polyamines in plant's response to various abiotic stresses [76,77].…”
Section: Intracellular Osmotic Adjustment and Osmoprotectantsmentioning
confidence: 99%
“…While ABA appears to be a key regulator in stomatal closure, both salicylic acid (SA) and hydrogen peroxide, which are produced under several modes following pathogen attack and stress stimuli, are also involved. Indeed, SA and hydrogen peroxide have been both shown to halt pathogen penetration inside the plant body [59][60][61]. Recently, Ziemann et al [62] reported that through the activity of a Papain-like cysteine protease, the immune signaling peptide 1 (ZIP1) is matured from its pro-peptide, and serves as an activator of SA signaling via transcriptional upregulation.…”
Section: Papain-like Cysteine Proteasesmentioning
confidence: 99%
“…Emerging interest has been added to study PAs in halophytes in salt tolerance ( Bueno and Cordovilla, 2019 ), emphasizing the regulatory role of polyamines in abiotic stress as hub molecules ( Sequera-Mutiozabal et al., 2017 ). Cooperating with other plant hormones such as cytokinin ( Černý et al., 2013 ) and interacting with nitrogen in stress responses make them able to fine tune the proper C/N ratio in order to achieve the optimal conditions for growth or stress responses ( Paschalidis et al., 2019 ). Moreover, PAs reprogramming oxidative and nitrosative status of salt exposed citrus plants could affect their redox status ( Tanou et al., 2014 ).…”
Section: Other Compounds With Potential Functions In Root Halotropismmentioning
confidence: 99%